Developing the Total Disability Index Based on an Analysis of the Interrelationships and Limitations of Oswestry and Neck Disability Index. Issue 1 (January 2016) - Spiegel, Matthew A.; Lafage, Renaud; Lafage, Virginie; Ryan, Devon; Marascalchi, Bryan; Trimba, Yuriy; Ames, Christopher; Harris, Bradley; Tanzi, Elizabeth; Oren, Jonathan; Vira, Shaleen; Errico, Thomas; et al.
Abstract : Study Design: Retrospective. Objective: This study assessed the feasibility of combining Oswestry and Neck Disability Index (ODI and NDI) into 1 shorter "Total Disability Index" (TDI) from which reconstructed scores could be computed. Summary of Background Data: ODI and NDI are not pure assessments of disability related to back and neck, respectively. Because of similarities/redundancies of questions, ODI scores may be elevated in neck-pain patients and the converse is true for NDI in back-pain patients. Methods: Spine patients completed ODI and NDI, and complaints were recorded as back pain (BP), neck pain (NP), or both (BNP). Questionnaire scores were compared across cohorts via descriptives and Spearman ( ρ ) correlations. In exploring the feasibility of merging ODI/NDI, TDI was constructed from 9 ODI and 5 NDI items. Extracting questions from TDI, reconstructed 9-item rODI and 10-item rNDI indices were formed and compared with true ODI/NDI. Results: There were a total of 1207 patients: 741 BP, 134 NP, and 268 BNP. Mean ODI was 37 ± 21 and mean NDI was 32 ± 21. Patients with concurrent BP and NP had significantly more disability. Seventy-eight patients of 134 (58%) patients with NP only had at least "moderate disability" by ODI and 297 of 741 (40%) patients with back pain only, had at least "moderate disability" by NDI. ODI versus NDI correlation was ρ = 0.755; ODI versus reconstructed rODI correlated at ρ = 0.985, and NDI versus reconstructed rNDI correlated at ρ = 0.967 ( P < 0.01). Conclusion: Elevated ODI/NDI scores in patients with isolated complaints show that disability in 1 region affects scores on both surveys. This study constructed a 14-item TDI that represents every domain of ODI/NDI with exception of ODI "Sex Life." From this TDI, reconstructed scores correlated near perfectly with true scores. TDI provides a more global assessment of spinal disability and is a questionnaire that reduces the time burden to patients. The TDI allows for simultaneous assessment of back, neck, and global spinal disability. Level of Evidence: 2